2018
DOI: 10.14417/ap.1245
|View full text |Cite
|
Sign up to set email alerts
|

Crianças em acolhimento residencial: Conteúdo temático das suas narrativas de vida

Abstract: A narrativa constitui uma unidade semântica em forma de história que permite ao ser humano dar sentido à sua experiência. A investigação na área não tem sido conclusiva quanto à capacidade das crianças que vivenciaram maus-tratos integrarem estas experiências nas suas narrativas de vida. Alguns investigadores defendem que os maus-tratos afetam a capacidade mnésica das crianças, dificultando a recordação e a referência destas experiências; outros defendem que experiências traumáticas podem até ser melhor record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
4
0
1
Order By: Relevance
“…These results stress that adaptation to the institutional environment is largely related to the personal characteristics of each child and/or adolescent (Baker et al, 2005;Brady & Caraway, 2002;Magalhães & Calheiros, 2014;Patrício et al, 2016), being particularly important to consider these dimensions for understanding adaption processes and challenges. Previous studies have found sex differences considering attachment and adaptation to institutional environments (Baker et al, 2005, D´Aroz & Stoltz, 2012, Mikulincer & Shaver, 2007Teixeira et al, 2018), nevertheless, considering the scarcity of results, additional knowledge should be produced on the processes underlying psychosocial adaptation and sex in youth in RCC. In what concerns age, although Baker et al (2005) found that children/younger adolescents (<12 years) could exhibit higher conflict behaviors during the transition to a residential setting, considering age range and the transition challenges, these results could address distinctive processes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These results stress that adaptation to the institutional environment is largely related to the personal characteristics of each child and/or adolescent (Baker et al, 2005;Brady & Caraway, 2002;Magalhães & Calheiros, 2014;Patrício et al, 2016), being particularly important to consider these dimensions for understanding adaption processes and challenges. Previous studies have found sex differences considering attachment and adaptation to institutional environments (Baker et al, 2005, D´Aroz & Stoltz, 2012, Mikulincer & Shaver, 2007Teixeira et al, 2018), nevertheless, considering the scarcity of results, additional knowledge should be produced on the processes underlying psychosocial adaptation and sex in youth in RCC. In what concerns age, although Baker et al (2005) found that children/younger adolescents (<12 years) could exhibit higher conflict behaviors during the transition to a residential setting, considering age range and the transition challenges, these results could address distinctive processes.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, there seems to be significant variability in the quality of protection and care provided in RCC, with important implications for the development of children and adolescents (e.g., Costa et al, 2019). Therefore, residential care can be a measure of promotion and protection, by promoting not only well-being, but also more adaptive relational and behavioral patterns in adolescents (Teixeira et al, 2018). Moreover, residential care can provide a space of protection, enabling the development of safe relationships (Mota & Matos, 2015;Siqueira & Dell´Aglio, 2006.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Esta abordagem, qualitativa e em profundidade, evidenciou uma grande variabilidade inter-individual, habitualmente esbatida nas abordagens quantitativas. Os resultados podem ser interpretados como uma grande diversidade de respostas às situações de adversidade que reforçam o não determinismo das experiências traumáticas e contribuem para a construção de narrativas adaptativas, já encontrada em estudos com outro tipo de populações com potenciais experiências traumáticas na área do acolhimento residencial (Teixeira, Silva, & Henriques, 2018).…”
Section: Tarefa De Escrita Expressiva Enquanto Método De Análise De Eunclassified
“…Although children’s removal from their families is justified by the urgency of their protection and security, this event and their entry into institutional care have a detrimental impact on their well-being and psychological adjustment. Following their removal, most children display externalization and internalization behaviors [ 3 , 4 ] and insecurity and greater disorganization in their attachment relations [ 5 , 6 , 7 ], and this has a highly negative impact on their life [ 8 ]. Following removal from the family and during their placement in foster care, children have to cope with the emotional impact triggered by multiple losses as well as with the need to adapt to new contexts [ 9 ].…”
Section: Introductionmentioning
confidence: 99%